Developing a Message Interface Architecture for Android Operating Systems - Ahamed, Mithun (American Scientific Research Journal for Engineering, Technology, and Sciences, 2015)
User Interface is an essential part of the field of Human–computer interaction (HCI). It’s involves the study, planning, design and uses of the interaction between people (users) and computers or machines. In modern human lifethis is essential such as mobile devices. We usually contact peoples via mobile devices, in such a way phone call and message passing, and this is very easiest way to contact with others. The intention of this paper is to provide an overview, analysis and proposed an idea of easy and light of message interface architecture for android operating system, which is most useable mobile operating systems in world. In generally we can contact with people through the message passing- on specific group messages or specific peoples. The overview include the basic definitions, a survey of traditional existing technologies of message interface architecture used in android devices, and finally the proposed idea and architecture of message interface for android devices. This paper also offers a comprehensive number of references for each concept, method, and application fields of interface design of HCI.